THE ARTISTIC AND SUFI ESSENCE OF THE CONCEPTS OF HEAVEN AND EARTH IN ALISHER NAVOI’S “LISON UT-TAYR” - Abdusalimov Suhrob Rustamovich (The Conference Hub, 2025)
This article analyzes the artistic and Sufi-philosophical interpretation of the concepts of heaven and earth in Alisher Navoi’s renowned work Lison ut-Tayr. In the text, heaven symbolizes spiritual ascent and the pursuit of divine truth, while earth represents the material world and the human ego. Through the allegorical journey of birds, the poem illustrates the soul's path toward spiritual perfection. The study explores how key Sufi notions such as fanā (self-annihilation), baqā (subsistence in God), nafs (ego), and ma‘rifa (gnosis) are reflected in the poetic structure and imagery of the work. The article also highlights the relevance of Navoi’s spiritual ideas in fostering modern moral education and promoting social harmony.
Keywords: Alisher Navoi, Lison ut-Tayr, heaven and earth, Sufism, poetic interpretation, spiritual ascent, moral perfection, nafs, fanā, ma‘rifa, journey of the birds, symbolic imagery, mystical worldview.